Evaluation of the Hg²⁺ binding potential of fulvic acids from fluorescence excitation–emission matrices - Berkovic, Andrea Mariela (2013)
The effect of Hg²⁺ on the fluorescence intensity of three fulvic acids (Pahokee Peat, Pony Lake and Suwannee River) was studied. The fluorescence intensity decreased in the presence of added Hg²⁺, while the fluorescence lifetimes were independent of the concentration of Hg²⁺ in solution. These results are indicative of ground-states association between the fulvic acids and Hg²⁺ with formation of stable non-fluorescent complexes (static quenching process). The analysis of the excitation–emission matrices with the Singular Value Decomposition (SVD) and Multivariate Curve Resolution – Alternating Least Squares (MCR-ALS) methods provided additional valuable information regarding the binding properties between Hg²⁺ ions and specific fluorescence components of the fulvic acids. The three fulvic acids were shown to contain the same three groups of fluorophores characterized by excitation/emission pairs in the following regions: (320–330 nm/425–450 nm), (370–375 nm/465–500 nm), (290–295 nm/370–395 nm). These pairs are almost not affected by the change of pH from 2.0 to 7.0. Ryan–Weber and modified Stern–Volmer methods were used to analyze the static fluorescence quenching of the individual components. Similar conditional stability constants of Hg²⁺ binding for the three components were found by both methods. The obtained log K values are in the range of 4.4 to 5.4.